Narcotics Related Deaths in the Kabul Forensic Medicine Center in 2018 and 2019 - Paigham, Abdul Manan; Anwari, Mohammad Taqi; Seraj, Palwasha (Eximia, 2023)
Introduction: Narcotic drugs and psychotropic substances are substances that, even in small quantities, can lead to substantial changes in the body, mind, or both. These substances have the ability to cross the blood-brain barrier and disrupt mood and perception. Examples of such substances include opiates, alcohol, hashish, cocaine, and 3,4-Methylenedioxymethamphetamine (commonly known as ecstasy or the drug "K"). Deaths resulting from narcotic poisoning refer to cases in which one or more narcotics are found in the body. Objectives: obtaining the prevalence of death due to narcotic drugs and psychotropic in forensic cases Method: The research was conducted through descriptive cross sectional study in Kabul Forensic Medicine Center in the year 2019 and 2018. Results: Out of 2838 cases that were referred to the Kabul Forensic Medicine center in the year 2019 and 2018, (14%) were due to narcotic drugs and the rest were due to other causes of death. Deaths due to narcotic drugs in 2019, compared to 2018, showed an increase of 17.47%. The majority of cases were in the range of 21-40 years (an average of 30 years) which included 58.2 % of entire cases: 97% of the cases were males, 57.5% were single, most of them were unemployed (39.3%), low educated and illiterate cases were 53.39%, and the lowest cases were with higher education (8.98%). The highest incidence happened in the winter (51.69%), and the lowest in the summer (13.8%). The most common cause of narcotics-related death were opiates (75.7%) and a significant of the narcotics were MDMA (please mention the complete form at least once) (5.8%). Most cases occur in the first (17%), fifth (16%), eighth (15%) and third (11.65%) security districts of Kabul city Conclusion: narcotic -related death make up about one-seventh of all forensic cases, which are on the rise, mostly among young, male, single, illiterate, unemployed, and low-income people. Most of the causes of drug-related deaths are opium and addicts. The significant point of cases was MDMA (K tablet) (5.8%), which has become common among young people in recent years. Most incidents occur in the winter and from central and western parts of Kabul.